A clinically compatible drug‐screening platform based on organotypic cultures identifies vulnerabilities to prevent and treat brain metastasis. Issue 3 (17th February 2022) - Zhu, Lucía; Retana, Diana; García‐Gómez, Pedro; Álvaro‐Espinosa, Laura; Priego, Neibla; Masmudi‐Martín, Mariam; Yebra, Natalia; Miarka, Lauritz; Hernández‐Encinas, Elena; Blanco‐Aparicio, Carmen; Martínez, Sonia; Sobrino, Cecilia; et al.
Abstract: We report a medium‐throughput drug‐screening platform (METPlatform) based on organotypic cultures that allows to evaluate inhibitors against metastases growing in situ . By applying this approach to the unmet clinical need of brain metastasis, we identified several vulnerabilities. Among them, a blood–brain barrier permeable HSP90 inhibitor showed high potency against mouse and human brain metastases at clinically relevant stages of the disease, including a novel model of local relapse after neurosurgery. Furthermore, in situ proteomic analysis applied to metastases treated with the chaperone inhibitor uncovered a novel molecular program in brain metastasis, which includes biomarkers of poor prognosis and actionable mechanisms of resistance. Our work validates METPlatform as a potent resource for metastasis research integrating drug‐screening and unbiased omic approaches that is compatible with human samples. Thus, this clinically relevant strategy is aimed to personalize the management of metastatic disease in the brain and elsewhere. Synopsis: A novel drug‐screening platform compatible with patient‐derived samples identifies effective therapies to prevent brain metastasis. METPlatform is a novel drug‐screening strategy to identify vulnerabilities of metastasis while colonizing organs ex vivo . METPlatform identified hits that were confirmed in vivo as effective against brain metastasis. METPlatform allows to dissect the molecular mechanisms downstream of target inhibition using omic approaches. METPlatform has a potential value as a patient "avatar". Abstract : A novel drug‐screening platform compatible with patient‐derived samples identifies effective therapies to prevent brain metastasis.